My E-Wallet / Nur Hazwani Mohamad Roseli … [et al.] - Mohamad Roseli, Nur Hazwani; Shafudin, Salwa; Mohd Nawawi, Nadzirah; Md Othman, Nafisah; Shadan, Nur Syareena; Md Ali, Nur Khairina (Division of Research and Industry Linkages, 2017)
According to Utusan Malaysia, snatch theft have been donated highest crime index in Malaysia. From January until May 2017 over 134 cases have been reported to Polis Diraja Malaysia (PDRM). Due to this case we come out with one innovation which is My E-Wallet. This high security wallet that requires owner's fingerprint to gain entry. It is made of carbon fiber, this wallet is a water-proof and scratch proof. By using the fingerprint authentication, it can be taught to recognize up to 3 fingerprints, requiring a simple swipe at the wallet to unlock it. The advantage of this product is it can help the owner to locate the wallet if it gone missing by using the GPS that place in this wallet. The features of this product are fingerprint authentication, GPS technology, electronic latch and buzzer. The target market for My E-Waliet is specialized for upper class women who works tremendously in career. Which at the range of age at 25 and above, live in urban places such as Kuala Lumpur, Selangor, Perak and Johor Bahru through the higher statistic. Moreover, this wallet also produced for person who quite clumsy and do not aware with their own wallet. So, with this initiative, we can reduce the missing wallet among people and at the same time, reduce the theft in the Malaysia. This wallet will be potential to commercialized because it will help the owner to found their wallet if it being stole using the high technology that we have been applied in this product.